2006
DOI: 10.1007/s00109-006-0108-7
|View full text |Cite
|
Sign up to set email alerts
|

Common variants in the TCF7L2 gene and predisposition to type 2 diabetes in UK European Whites, Indian Asians and Afro-Caribbean men and women

Abstract: Common variants of TCF7L2, encoding a beta-cell-expressed transcription factor, are strongly associated with increased risk of type 2 diabetes (T2D). We examined this association using both prospective and case-control designs. A total of 2,676 healthy European white middle-aged men from the prospective NPHSII (158 developed T2D over 15 years surveillance) were genotyped for two intronic SNPs [rs 7903146 (IVS3C>T) and rs12255372 (IVS4G>T)] which showed strong linkage disequilibrium (D' = 0.88, p<0.001; R(2)=0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
101
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(116 citation statements)
references
References 26 publications
12
101
3
Order By: Relevance
“…It is noteworthy that the association between the SNP in TCF7L2 and type 2 diabetes has consistently been observed in different ethnic groups [14,15], which supports the reliability of both previous studies as well as our present study. The mechanism of action of TCF7L2 in glucose metabolism and the pathogenesis of type 2 diabetes has yet to be elucidated, but it is possible that TCF7L2 has a role in regulating glucose-sensitive insulin secretion from beta cells.…”
Section: Discussionsupporting
confidence: 93%
“…It is noteworthy that the association between the SNP in TCF7L2 and type 2 diabetes has consistently been observed in different ethnic groups [14,15], which supports the reliability of both previous studies as well as our present study. The mechanism of action of TCF7L2 in glucose metabolism and the pathogenesis of type 2 diabetes has yet to be elucidated, but it is possible that TCF7L2 has a role in regulating glucose-sensitive insulin secretion from beta cells.…”
Section: Discussionsupporting
confidence: 93%
“…Five single nucleotide polymorphisms (SNPs) (rs12255372, rs7903146, rs7901695, rs11196205, and rs7895340) within the LD block also showed similarly robust associations with type 2 diabetes (6). Further studies in other European populations, African Americans, Mexican Americans, and Asian Indians confirmed the strong associations with an estimated population attributable risk of 17-28% (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Several genome-wide association studies independently confirmed the strong associations of SNP rs7903146 in the TCF7L2 locus with type 2 diabetes (23)(24)(25)(26).…”
mentioning
confidence: 89%
“…Polymorphisms of TCF7L2 have been associated with diabetes in numerous studies [1][2][3] and the magnitude of risk conferred by TCF7L2 variants is greater than for any previously described common variant. The single nucleotide polymorphism (SNP) rs7903146 is the most highly associated of the known variants and is associated with a 40% increased risk of diabetes per allele [4].…”
Section: Introductionmentioning
confidence: 96%